2017
DOI: 10.4049/jimmunol.1700943
|View full text |Cite
|
Sign up to set email alerts
|

A Hard(y) Look at B-1 Cell Development and Function

Abstract: A small population of B cells exists in lymphoid tissues and body cavities of mice that is distinct in development, phenotype and function from the majority (B-2) B cell population. This population, originally termed “Ly1” and now “B-1”, has received renewed interest as an innate-like B cell population of fetal-derived hematopoiesis, responsible for natural antibody production and rapid immune responses. Molecular analyses have begun to define fetal and adult hematopoiesis, while cell-fate mapping studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 112 publications
1
105
0
Order By: Relevance
“…However, further investigation with additional cell surface markers demonstrated that within mature splenic B cells, there was an increase in the proportion of IgM + IgD low cells (Figure 5G), indicating an immature phenotype. Evaluating CD19 int B220 int populations revealed cells in Vhl cKO spleens expressing an IgM+ IgD low staining pattern ( Figure 5G), reminiscent of the staining pattern found on plasma B cells and the "natural antibody" producing innate-like B-1 B cells, which are normally not found in the spleen [30]. Taken together, our data demonstrate that osteocytic Vhl deletion has dramatic effects on hematopoiesis in the bone marrow, and suggests that these changes in the bone marrow result in major effects on hematopoiesis and B cell development in the spleen.…”
Section: Cell-extrinsic Effects Of Osteocytic Vhl Deletion On Hematopmentioning
confidence: 83%
“…However, further investigation with additional cell surface markers demonstrated that within mature splenic B cells, there was an increase in the proportion of IgM + IgD low cells (Figure 5G), indicating an immature phenotype. Evaluating CD19 int B220 int populations revealed cells in Vhl cKO spleens expressing an IgM+ IgD low staining pattern ( Figure 5G), reminiscent of the staining pattern found on plasma B cells and the "natural antibody" producing innate-like B-1 B cells, which are normally not found in the spleen [30]. Taken together, our data demonstrate that osteocytic Vhl deletion has dramatic effects on hematopoiesis in the bone marrow, and suggests that these changes in the bone marrow result in major effects on hematopoiesis and B cell development in the spleen.…”
Section: Cell-extrinsic Effects Of Osteocytic Vhl Deletion On Hematopmentioning
confidence: 83%
“…Thus, the enhanced ability of B cells in younger Sost -/-mice to respond to NP-Ficoll (a TI-2 antigen) in vivo, is intriguing. Responses to Tindependent antigens can be mediated by innate-like B cells, such as unconventional B-1 lymphocytes (a fetally-derived cell population that persists during adulthood in the peritoneal cavity and mucosa, and may also develop postnatally in the BM (25,26) ), and splenic marginal zone B cells (27) . Further investigation is required to determine the mechanisms underlying the enhanced IgG3 response to Tindependent antigens in the younger Sost -/mice, such as a simple decrease in conventional B lymphocytes, and if sclerostin deficiency promotes expansion, activation and/or changes in Fc receptor expression in innate-like B cell subsets (28) .…”
Section: Discussionmentioning
confidence: 99%
“…33 The present review comprises a description of the development of the Bregs, their various phenotypes, their functions, and their role in transplantation. Rothstein and colleagues 35,36 have proposed that B1 cells are characterized by the expression of CD20, CD27, CD43, and CD70. 34 In human, the phenotypic characteristics of B1 remain controversial.…”
Section: Regulatory B Cells (Bregs) Identified In Mouse and In Humanmentioning
confidence: 99%
“…34 In human, the phenotypic characteristics of B1 remain controversial. Rothstein and colleagues 35,36 have proposed that B1 cells are characterized by the expression of CD20, CD27, CD43, and CD70. More recently, Quach et al 37 have suggested an additional phenotypical marker for B1 cells in human, CD38.…”
Section: The De Velopment Of B Cell S and B Reg Smentioning
confidence: 99%